Resposta :
Resposta:
26
Explicação passo a passo:
180 - {[[tex]4^{3}[/tex] : ( [tex]3^{2}[/tex] - 1 ) + [tex]2^{2}[/tex] . 3] . [tex]2^{3}[/tex] } + 6 =
180 - {[[tex]4^{3}[/tex] : ( 3 . 3 - 1) = ( 9 - 1 ) = 8
180 - {[[tex]4^{3}[/tex] : 8 + [tex]2^{2}[/tex] . 3] . [tex]2^{3}[/tex] } + 6 =
180 - {[[tex]4^{3}[/tex] : 8 + [tex]2^{2}[/tex] . 3] = 4 . 4 . 4 = 64
64 : 8 = 8
8 + 2 . 2 . 3
2 . 2 = 4 = 4 . 3 = 12
8 + 12 = 20
180 - {20 . [tex]2^{3}[/tex] } + 6 =
2 . 2 . 2 = 8
20 . 8 = 160
180 - 160 + 6 =
180 - 160 = 20 + 6 = 26